HISTOPATOLOGI HATI MENCIT PASCA PEMBERIAN SUSPENSI KEPEL (Stelechocarpus burahol) SECARA INTRAGASTRIK SELAMA 14 HARI The Histopathology of Mice Liver Treated by Kepel (Stelechocarpus burahol) Suspension Intragastrically for 14 days - Eva Harlina; Siti; Huda S Darusman; Gita Alvernita (Universitas Pakuan, 2012)
This aim of this study was to examine the effect of Kepel (Stelechocarpus burahol) to the mice hepatocytes. Thirty male mice of 4 week aged were divided into three groups;control group was treated by aquadest, Dose 1x group was treated by 2.6 mg/g BW/daykepel powder (0.5 ml kepel suspension/day), and Dose 5x group was treated by 13 mg/gBW/day kepel powder (1.0 ml kepel suspension/day). The treatment was intragastricallyfor 14 days. The mice were euthanized and necropsy followed by the liver collection forhistopathology assay. The histopathological examination of liver showed hydropicdegeneration, cell death and extramedullary hematopoietic observed on mice hepatocytes.The ANOVA analysis showed that kepel caused increase significantly (p0.05) ofhydropic degeneration and decrease significantly (p0.05) of cell death of micehepatocytes.Key words: Stelechocarpus burahol, hydropic degeneration, cell death, extramedullary hematopoietic